Electrospun poly(3-hydroxybutyrate-co-3-hydroxyvalerate)/polyethylene oxide (PEO) microfibers reinforced with ZnO nanocrystals for antibacterial and antibiofilm wound dressing applications - Mahamuni-Badiger, Pranjali P.; Patil, Pooja M.; Patel, Pratikshkumar R.; Dhanavade, Maruti J.; Badiger, V. Manohar; Marathe, Yogesh N.; Bohara, Raghvendra A. (New Journal of Chemistry, 2020)
Biocompatible and biodegradable polymers are extensively used in designing wound dressing materials. The present investigation deals with the preparation of a unique blend of zinc oxide (ZnO) nanoparticles incorporated in poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV)/polyethylene oxide (PEO) microfibersviaan electrospinning technique for antibacterial, antibiofilm and wound dressing applications. This composite was prepared by incorporating previously synthesized ZnO NPs with better antibacterial and antibiofilm activity in PHBV-PEO (4 : 1) polymers in chloroform solution. Scanning electron microscopy (SEM) and Fourier transform infrared (FT-IR) spectroscopy confirmed that ZnO NPs were incorporated in the PHBV-PEO microfibers. The synthesized microfibers exhibited enhanced mechanical properties after the incorporation of ZnO NPs. The results of antibacterial and antibiofilm activity of the prepared microfibers revealed that the incorporated ZnO NPs in different concentrations (1%, 3%, and 5%) showed different degrees of antibacterial activity against pathogenic Gram-positiveStaphylococcus aureus(NCIM 2654) and Gram-negativePseudomonas aeruginosa(NCIM 5032), which are the main bacteria found in wound infections. The PHBV-PEO-ZnO microfibers exhibited excellent hemocompatibility with improved swelling behavior after the incorporation of ZnO NPs.In vitrocytotoxicity assays revealed the non-toxic nature of the prepared PHBV-PEO-ZnO microfibers. The current work confirms that utilizing a unique blend of the biodegradable, biocompatible, thermoplastic and hydrophobic natural polymer PHBV with hydrophobic, biodegradable, non-toxic and synthetic polymer PEO with ZnO NPs holds great potential for use as an antibacterial and antibiofilm material for wound dressing applications.

In situ cross-linked nonaqueous polymer electrolyte for zinc-metal polymer batteries and hybrid supercapacitors - Vijayakumar, Vidyanand; Ghosh, Meena; Kurian, Maria; Torris, Arun; Dilwale, Swati; Badiger, V. Manohar; Winter, Martin; Nair, Jijeesh Ravi; Kurungot, Sreekumar (Small, 2020)
This work reports the facile synthesis of nonaqueous zinc-ion conducting polymer electrolyte (ZIP) membranes using an ultraviolet (UV)-light-induced photopolymerization technique, with room temperature (RT) ionic conductivity values in the order of 10(-3)S cm(-1). The ZIP membranes demonstrate excellent physicochemical and electrochemical properties, including an electrochemical stability window of >2.4 V versus Zn|Zn(2+)and dendrite-free plating/stripping processes in symmetric Zn||Zn cells. Besides, a UV-polymerization-assisted in situ process is developed to produce ZIP (abbreviated i-ZIP), which is adopted for the first time to fabricate a nonaqueous zinc-metal polymer battery (ZMPB; VOPO4|i-ZIP|Zn) and zinc-metal hybrid polymer supercapacitor (ZMPS; activated carbon|i-ZIP|Zn) cells. The VOPO(4)cathode employed in ZMPB possesses a layered morphology, exhibiting a high average operating voltage of approximate to 1.2 V. As compared to the conventional polymer cell assembling approach using the ex situ process, the in situ process is simple and it enhances the overall electrochemical performance, which enables the widespread intrusion of ZMPBs and ZMPSs into the application domain. Indeed, considering the promising aspects of the proposed ZIP and its easy processability, this work opens up a new direction for the emergence of the zinc-based energy storage technologies.
Keywords: nonaqueous electrolytes; polymer electrolytes; postlithium batteries; Supercapacitors; zinc-metal batteries

Design and synthesis of a new topical agent for halting blood loss rapidly: a multimodal chitosan-gelatin xerogel composite loaded with silica nanoparticles and calcium - Patil, Gokul; Torris, Arun; Suresha, P. R.; Jadhav, Sachin; Badiger, V. Manohar; Ghormade, Vandana (Colloids and Surfaces B-Biointerfaces, 2021)
Uncontrolled hemorrhage often causes death during traumatic injuries and halting exsanguination topically is a challenge. Here, an efficient multimodal topical hemostat was developed by (i) ionically crosslinking chitosan and gelatin with sodium tripolyphosphate for (ii) fabricating a robust, highly porous xerogel by lyophilization having 86.7 % porosity, by micro-CT and large pores similar to 30 mu m by SEM (iii) incorporating 0.5 mg synthesized silica nanoparticles (SiNPs, 120 nm size, -22 mV charge) and 2.5 mM calcium in xemgel composite that was confirmed by FTIR analysis with peaks at 3372, 986 and 788 cm(-1), respectively. XPS analysis displayed the presence of SiNPs (Si2p peak for silicon) and calcium (Ca2p1, Ca2p3 transition peaks) in the composite. Interestingly, in silico percolation simulation for composite revealed interlinked 800 mu m long-conduits predicting excellent absorption capacity and validated experimentally (640 % of composite dry weight). The composite achieved >16-fold improved blood clotting in vitro than commercial Celox and Gauze through multimodal interaction of its components with RBCs and platelets. The composite displayed good platelet activation and thrombin generation activities. It displayed high compressive strength (2.45 MPa) and withstood pressure during application. Moreover, xerogel composite showed high biocompatibility. In vivo application of xerogel composite to lethal femoral artery injury in rats achieved hemostasis (2.5 min) significantly faster than commercial Celox (3.3 min) and Gauze (4.6 min) and was easily removed from the wound. The gamma irradiated composite was stable till 1.5 yr. Therefore, the xerogel composite has potential for application as a rapid topical hemostatic agent.
Keywords: Hemostatic; Polymer; silica nanoparticles; Xerogel